Analysis and classification of historical-oriented Internet sources - Peleschyshyn, Andriy; Bilushchak, Тetiana (Lviv Polytechnic Publishing House, 2015)
The article analyzes the online sources with historical information available there. The Internet sources are analyzed according to the groups and types of information they contain.
Keywords: Internet-sources; social networks; search engines; classification; types; primary sources; secondary sources